Analisis Faktor yang Berhubungan dengan Kejadian Phlebitis pada Pasien yang Terpasang Kateter Intravena di Ruang Bedah Rumah Sakit Ar. Bunda Prabumulih - Wahyu Rizky (Alma Ata University Press, 2016)
Incidence of phlebitis is an indicator of the quality of hospital services with minimal rate of ≤1,5% standard. The incidence of phlebitis in Hospital AR. Bunda Prabumulih still high ranging from 8% to 17%. Highest incidence of phlebitis is in February amounted to 17%. This research to analyze the factors related incidence phlebitis in patient intravenous catheter. This research use description of the correlation with cross sectional method. This research was conducted in the surgical room (ibnu sina) AR. Bunda Prabumulih Hospital. Involving 92 respondens using total sampling and observation sheet as a measuring instrument. The method of analysis used in this research is both univariate and bivariate data. The result this test analysis research show that there is relationship between age and type of intravenous fluid toward phlebitis with significant influence p-value=0.000. In addition, intravenous catheter care and comorbidities no significant relationship with the incidence of phlebitis with p-value=0.643. The result is expected to be a reference to hospital, mainly for medical personnel in carrying out act of intravenous catheters still consider the factors supporting the occurence of phlebitis.